Manual of vascular surgery - Khanna AK; Puneet (New Delhi : Jaypee Brothers Medical Publishers, 2010)
Describe las condiciones vasculares y las técnicas, investigaciones y tratamientos en cirugía vascular.
Describing vascular conditions, and the techniques, investigations and treatments in vascular surgery.
Contents 1. Introduction to peripheral arterial disease 2. Clinical examination of a vascular case 3. Vascular imaging 4. Surgical exposure of vessels 5. Vascular sutures and anastomoses y otros 20 capítulos más
Keywords: BLOOD VESSELS -- SURGERY; CIRUGIA VASCULAR; .